CORRELATIONS BETWEEN SERUM LEVEL OF MATRIX METALLOPROTEINASE-9 (MMP-9) AND SERUM LEVEL OF TROPONIN-I IN PATIENT WITH ACUTE CORONARY SYNDROME (ACS) - Ruchanihadi Ruchanihadi; Budi Yuli Setianto; Hariadi Hariawan (Faculty of Medicine Universitas Gadjah Mada, 2011)
ABSTRACTBackground. The pathophysiology of acute coronary syndromes (ACS) is now accepted as the rupture or erosion of an atherosclerotic plaque, initially occurs at the shoulder of the plaque and is followed by intra-plaque thrombosis then spread to the vascular lumen and cause total partial vascular occlusion. MMP-9 is an extracellular matrix degrading enzyme that plays a crucial role in the breakdown of the fibrous cap of plaque and subsequent rupture in the pathogenesis of ACS. Cardiac troponins are currently the most sensitive and specific biochemical markers of myocytes necrosis.Objective. To know the correlation between serum level MMP-9 and serum level of Troponin-I in patients with ACSMethod. Study design was cross sectional. Data were collected by consecutive sampling from patients in ICCU board of RSUP Dr. Sardjito Yogyakarta, in June 2008-August 2010. A questionnaire was used to collect information from patient. After admission, peripheral venous blood was drawn once and measuring concentration of serum level of MMP-9 and Troponin-I before definitive thrombolysis. Data are expressed as means ± standard deviation (SD). Correlation between serum level of MMP-9 and serum level of Troponin-I were assessed using Spearman’s rank correlations test. A value of p<0.05 was considered statistically significant.Result. There were 139 patients with ACS and comprising 63 patients with STEMI, 27 patients with NSTEMI, and 49 patients with UAP. Means±SD of Troponin-I from all of samples was 9.49±10.47 ng/dL. Mean±SD of MMP-9 from all of samples was 1296.06±729.97 ng/dL. There were significant correlations between MMP-9 and Troponin-I in patients with ACS (r=0.34, p=0.000).Conclusion. There were significant correlations between MMP-9 and Troponin-I in ACS patients in ICCU RSUP Dr. Sardjito Yogyakarta. Keywords: ACS, MMP-9, Troponin-I